Performance Analysis of a 1-1 Shell-and-Tube Intercooler for Compressed Air Cooling Systems - Farida Diyah Hapsari; Hana Nikma Ulya; Esther Mutiara Santallum Ekklesia Tibalia; Sabrianah Badaruddin; Alif Nur Laili Rachmah (Equilibrium Journal of Chemical Engineering, 2026)
This study presents an evaluation of a 1-1 shell-and-tube heat exchanger (Intercooler-2) utilized in a multi-stage air compressor. The evaluation was conducted using plant operational data and classical heat exchanger analysis methods, including heat balance, overall heat transfer coefficient under clean (Uc) and operating (Ud) conditions, dirt factor (Rd) and pressure drop (ΔP). The calculation results show a heat transfer rate of 557,640.622 Btu/h with a true temperature difference of 113.774 °F, indicating an adequate thermal driving force. The flow on the shell side is in the turbulent regime (Re ≈ 79,952), while the tube side shows laminar flow (Re ≈ 829), which limits the optimization of convective heat transfer of water as a cooling medium. The overall heat transfer coefficient under clean conditions of 25.627 Btu/h.ft².°F decreased to 23.125 Btu/h.ft².°F due to a fouling factor (Rd) of 0.004. The pressure drop values on both sides are still well below the permitted limits, so the unit is declared operationally feasible. However, the presence of fouling and laminar flow regime on the tube side indicates the potential for performance improvement thru optimization of water flow rate and periodic cleaning. This study emphasizes the importance of periodic performance evaluation to maintain the efficiency and reliability of heat exchanger operations in air compression systems.